2021
DOI: 10.48550/arxiv.2107.03029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Overview on the Application of Graph Neural Networks in Wireless Networks

Abstract: With the rapid enhancement of computer computing power, deep learning methods, e.g., convolution neural networks, recurrent neural networks, etc., have been applied in wireless network widely and achieved impressive performance. In recent years, in order to mine the topology information of graphstructured data in wireless network as well as contextual information, graph neural networks have been introduced and have achieved the state-of-the-art performance of a series of wireless network problems. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…All BSs are assumed to have the same maximum capacity in terms of radio resources (bandwidth and resource blocks) to simplify the traffic load normalization during the data pre-processing, and the calculations in Eqs. (12) and (21). The reason is that we are only interested in whether the original traffic load is preserved for each cell-switching scheme according to the introduced performance metrics, following the optimization constraint defined by Eq.…”
Section: Evaluation Configurationsmentioning
confidence: 99%
“…All BSs are assumed to have the same maximum capacity in terms of radio resources (bandwidth and resource blocks) to simplify the traffic load normalization during the data pre-processing, and the calculations in Eqs. (12) and (21). The reason is that we are only interested in whether the original traffic load is preserved for each cell-switching scheme according to the introduced performance metrics, following the optimization constraint defined by Eq.…”
Section: Evaluation Configurationsmentioning
confidence: 99%
“…Due to their localized nature, GNNs have also been applied to cooperative [30] and decentralized [31] control problems in networked systems. A review of the use of GNNs in wireless communication can be found in [32].…”
Section: Prior Workmentioning
confidence: 99%
“…Over the past few years, machine learning, and particularly deep learning, architectures have been increasingly used to address challenging problems in wireless communications, including those that fall under the umbrella of radio resource management (RRM), such as beamforming and power control [1][2][3]. More recently, solutions based on graph neural networks (GNNs), or in general, graph representation learning, have become more popular, mainly due to their desirable properties, such as permutation equivariance, size invariance, and stability to perturbations [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%